Mapping Potential Zones for Groundwater Recharge Using a GIS Technique in the Lower Khwae Hanuman Sub-Basin Area, Prachin Buri Province, Thailand - Kaewdum, Narongsak; Chotpantarat, Srilert (Frontiers in Earth Science, 2021)
The lower Khwae Hanuman sub-basin in Thailand suffers from water shortage during each dry season. As such, groundwater resources are an additional freshwater source in this region, in particular for cultivating activities. Thus, an understanding of the volume of groundwater recharge into the saturated zone is required. The objective of the study is to assess the groundwater recharge potential (GRP) using the weighted overlay analysis method by geographic information system (GIS) and finally checking the reliability of GRP map using observed specific capacity carried out by the Department of Groundwater Resources (DGR). The geological and hydrogeological features that affect groundwater potential are the lithology, land use, lineaments, drainage, slope, and soil. The weighting and rating of these six effective factors were determined by assessing the interrelationship of the main and minor influences of each factor based on several literature reviews, followed by a weighted overlay analysis with GIS, in association with groundwater recharge. The GRP can be classified in descending order: high, moderate, low, and very low, where about 33.9 km2 (2.26 % of the total area of 1,500 km2) had high recharge potentiality, located at the center of the area. Only 12.8% of the total precipitation (271.75 × 106 m3/y) infiltrated the groundwater aquifer, while the rest was lost by either surface runoff or evapotranspiration. The GRP sensitivity analysis index, lithology was the most efficient effective factor in GRP mapping. Most groundwater wells (>96% or 369 wells) were classified into the classes of low and moderated, which agree to the GRP zones. The first-hand recharge potential map and groundwater recharge information in this area can be used to establish an effective groundwater exploration program for agricultural activities; it is also used to appropriate sustainable yields from each groundwater basin to provide groundwater over the long-term, without negatively impacting the environment and without affecting the groundwater balance as it has recharge in the rainy seasons, which can use groundwater sustainably. It is in line with the sustainable development goals (SDGs) in goal number 6 of the UN.